Budidaya Maggot Untuk Pengelolaan Sampah Organik Dan Pakan Ternak Sebagai Upaya Kelestarian Lingkungan Di Dukuh Randu Kuning - A'yun, Sekar Isnanda Qurrota; Rafidah, Claritha Nasywa Nur; Kurniawan, Galih Sakti; Nafiah, Maratun; Lukmana, Dhefi Intan (Universitas Pahlawan Tuanku Tambusai, 2025)
The maggot farming program implemented in Dukuh Randu Kuning aims to address the issue of organic waste, which has long burdened the environment, while simultaneously enhancing the community's economic welfare. This initiative is designed to shift the community's perception of organic waste from a problem to a valuable resource. The approach includes intensive socialization about the impacts of organic waste, the introduction of maggot farming using Black Soldier Fly (BSF) larvae, live demonstrations of the farming process, and interactive discussions to address public inquiries. The program emphasizes sustainable waste management benefits, including significant waste volume reduction, the provision of affordable and high-protein animal feed, the production of eco-friendly compost, and the creation of new business opportunities. Implementation strategies involve initial facilitation, the formation of maggot farmer groups, regular monitoring and evaluation, and sustainability campaigns to expand the program's positive impact. Expected outcomes of this program include a reduction in organic waste volume, increased community income, and the creation of a cleaner and healthier environment. The program also supports organic farming by reducing dependence on chemical fertilizers. With a holistic approach, maggot farming serves not only as a technical solution for waste management but also as a strategic step toward economic empowerment and environmental preservation. This initiative could inspire similar regions facing comparable challenges.